2010
DOI: 10.1177/0885328210366489
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polymeric Capsules Obtained via Room Temperature Spray Drying: Preparation and Characterization

Abstract: The aim of this contribution is to determine the relationship existent between the chemistry and/or viscosity of some biodegradable polymer solutions and the morphology of micro- and nanospheres resulted after spray drying the solutions at room conditions either in the presence or in the absence of an encapsulated aqueous material. Using dichloromethane as solvent, the following polyesters were used to prepare 2 wt% solutions: polyhydroxybutyrate (PHB), polylactic acid (PLA), poly(lactic-co-glycolic acid) (PLG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Hydrogen peroxide H 2 O 2 encapsulated into biocompatible microcavities has been well studied as potential oxygen delivery materials for tissue engineering. Various polymer microspheres have been shown to encapsulate hydrogen peroxide for sustained release of oxygen, including polylactic acid and poly(methyl methacrylate) . Catalase has been incorporated into the system to catalyze the decomposition of the released H 2 O 2 into oxygen and water.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrogen peroxide H 2 O 2 encapsulated into biocompatible microcavities has been well studied as potential oxygen delivery materials for tissue engineering. Various polymer microspheres have been shown to encapsulate hydrogen peroxide for sustained release of oxygen, including polylactic acid and poly(methyl methacrylate) . Catalase has been incorporated into the system to catalyze the decomposition of the released H 2 O 2 into oxygen and water.…”
Section: Methodsmentioning
confidence: 99%
“…Urea and other decomposition products, however, are contaminants that limit use of the product as a source of H 2 O 2 . Other researchers have tried encapsulating H 2 O 2 in various polymer matrices, such as polylactic‐co‐glycolic acid, polylactic acid, and polymethylmethacrylate, to increase its stability. The results showed low encapsulation efficiencies of H 2 O 2 because of its high diffusivity.…”
Section: Introductionmentioning
confidence: 99%
“…Although research has been reported on the preparation of oil-filled polymer microcapsules by various techniques (Berkland et al, 2007;Dowding et al, 2004Dowding et al, , 2005Yow and Routh, 2006), there is limited research on the preparation of water-filled polymer microcapsules Bean et al, 2012). A few research groups have reported on the encapsulation of H 2 O 2 in polymers Stefanescu et al, 2011), however the microcapsules synthesized in these studies have very small amounts of encapsulated H 2 O 2 and quantitative H 2 O 2 release data are not presented in these studies.…”
Section: Introductionmentioning
confidence: 98%